Hubungan Dukungan Keluarga Dengan Kesehatan Mental Klien Yang Menjalani Pengobatan Diabete Melitus Di Puskesmas Telaga Biru - Rona Febriyona; Andi Nuraina Sudirman; Dea Ananda Febriyanti Bone (Jurnal Keperawatan Muhammadiyah, 2026)
Objective: to identify people with diabetes mellitus easily experience mental disorders or internalization disorders such as patients feeling sad and unhappy, patients are easily desperate, experiencing feelings of anxiety. Diabetics need support from their families because the family is the closest person who can play an active role in achieving compliance and successful treatment in people with diabetes mellitus Methods: This article with an analytical survey approach and using a cross sectional research design. The object of the study people and 36 people using accidental sampling technique that meet the inclusion and exclusion criteria. The research instrument uses family Support Questionnaire and Mental Health Questionnaire of Clients Undergoing Diabetes Mellitus Treatment). The data were analyzed with Chi-square. Results: The results showed the highest family support is the support of 29 people while the mental health of the patients is healthy as many as 27 people with a value of Vpalue=0.000 (<α 0.05). Conclusion: There is a a relationship of family support with the mental health of clients who are undergoing diabetes mellitus treatment at the Telaga Biru Health Center